KINERJA KOPERASI PERTANIAN: KASUS KOPERASI DI KABUPATEN ACEH TENGAH DAN BENER MERIAH - Devi Agustia; Nunung Kusnadi; Harianto Harianto (Universitas Teuku Umar, 2016)
The purpose of this research is to determine the performance cooperative of the organizationalaspects,financial aspects and business aspects. The approach used in this research is descriptive analysis. The measurement oforganizational performance and businessincludes the number of cooperative members, amount and characteristicsof the board and the employees, capital,business volume, SHU,and premium fee cooperative.Measurement of financial performance include the ratio of liquidity, solvabilitas and profitability based on the reports Annual Members Meeting (RAT) in 2014. The result showed that the human resources owned by cooperatives was quite good, the potential members and employees can be developed and improved both the quantity and quality.The financial condition of the cooperative has been able to generate profits from the management of capital, but still the cooperatives has not been able to guarantee its debts. The results also show that the cooperative has been able to manage its business activities are visible from the volume of business, SHU, and high premium fee. Cooperatives in Central Aceh and Bener Meriah regencies have been able to manage all the potentials for their business activities